DEPOSITIONAL SETTING OF THE DEVONIAN/CARBONIFEROUS BIOHERMAL BOL'SHAYA NADOTA CARBONATE COMPLEX, SUBPOLAR URALS - Skompski S.; Paszkowski M.; Krobicki M.; Kokovin K.; Korn D.; Tomaś A.; Wrzoek T. (My University, 2001)
Multi-stage development of carbonate buildups has been recognised in the Bol'shaya Nadota Carbonate Complex, in the vicinity of the town of Inta (Subpolar Urals). The growth of typical stromatoporoid-coral bioherms, characteristic of the Middle-Late Devonian stage, was terminated by the appearance of the shallow water oolitic facies, most probably at the beginning of the Famennian. During the Viséan stage the carbonate platform was reconstructed, but algalbrachiopod-coral bioherms were characterized by relatively small dimensions and an interfingering with organodetrital-oolitic facies. Sporadically, the inter-mound facies is represented by goniatite-bivalve coquinas with two new goniatite species: Goniatites olysya sp.nov. and Lusitanoceras kusinae sp.nov. The persistence of biothermal sedimentation in the Bol'shaya Nadota area is most probably caused by the specific position of the region on the boundary of two sedimentary-structural units: Lemva and Elets Zones, which corresponded to a basinal and a tectonically-active elevated part of a platform margin respectively. The overall biotic composition of the Carboniferous bioherms from Bol'shaya Nadota, situated in the northern periphery of Laurussia, falls generally within the diversity spectrum of Lower Carboniferous mounds described from the southern margin of the continent.
Keywords: Carboniferous; Devonian; Carbonate buildups; Subpolar Urals; Paleozoic::Carboniferous; Paleozoic::Devonian; Палеозой::Каменноугольная; Палеозой::Девонская